The Relationship Between Moodle-Based Learning Management System Usage and Employee Knowledge Retention in the Individual Development Program at BPJS Ketenagakerjaan - Rian Andrian; Muhamad Nursyahal Zein (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2026)
This study examines the relationship between Moodle-based Learning Management System (LMS) usage within the Individual Development Program (IDP) and employee knowledge retention at BPJS Ketenagakerjaan. A cross-sectional survey was distributed to IDP participants nationwide using a purposive, voluntary-response technique; after removing 73 duplicate submissions, 417 valid responses were analyzed (minimum required by the Slovin formula: 372). The instrument's 30 retained items (15 LMS-usage, 15 knowledge-retention) were all valid (r = 0.715–0.886 > r-table = 0.096) and reliable (Cronbach's Alpha 0.957–0.979). Regression residuals departed from normality, homoscedasticity, and strict linearity, so heteroscedasticity-robust (HC3) errors were used to confirm inference. The model (Y = 3.113 + 0.901X) showed a significant positive association between LMS usage and knowledge retention (robust t = 29.643, p < .001; F = 1008.233, p < .001), with usage associated with 70.84% of the variance in retention (R² = 0.7084). Greater LMS engagement is linked to stronger self-reported retention within the IDP, informing digital training design at BPJS Ketenagakerjaan. Given the cross-sectional, single-source design, findings should be read as associations rather than causal effects.